Evaluasi Keefektifan Rambu Lalu Lintas Dalam Meningkatkan Keselamatan Jalan Raya - Putri Permata A Harahap; Rian Todo Simanjuntak; Siti Zahra Siagian; Victoria Grace Daily; Yuli Indriani Lubis; Yeni Yolanda Simbolon; Ramsul Nababan (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This research uses a qualitative approach to evaluate the effectiveness of traffic signs in improving road safety in Indonesia. Through a series of methods, including direct observation, in-depth interviews, and documentation study, this research aims to understand how traffic signs contribute to road safety and what factors influence their effectiveness. The results show that traffic signs play an important role in controlling traffic flow and preventing accidents. However, their effectiveness is often hindered by several factors. First, a lack of understanding by road users about traffic signs. Second, poor maintenance of traffic signs. Third, weak law enforcement. Based on these findings, this research recommends several steps to improve the effectiveness of traffic signs. First, increasing public education about the importance of obeying traffic signs. Second, routine and quality maintenance and repair of traffic signs. Third, stronger and consistent law enforcement against traffic violations. This research hopes that with the implementation of these recommendations, the effectiveness of traffic signs in improving road safety can be increased.